A clinical perspective on escalating or de-escalating adjuvant therapy in HER2+ breast cancer. Issue 1 (2nd January 2019) - Esposito, Angela; Viale, Giulia; Criscitiello, Carmen; Curigliano, Giuseppe
ABSTRACT: Introduction : Patients with early HER2-positive breast cancer (BC) benefit from HER2-targeted systemic therapy. The endorsed standard adjuvant treatment for patients with early HER2-positive breast cancer is chemotherapy plus trastuzumab administered for 1 year. Areas covered : Several trials have investigated modifications of the standard treatment in terms of de-escalation by either shortening the duration or giving less resource-demanding regimens and in terms of escalation by either adding a second anti-HER2 agent or extending the duration of HER2-targeted treatment for more than 12 months. In this perspective, we would offer a comprehensive view of these trials and discuss their findings. Expert commentary : At the current state of knowledge, there are still open questions regarding the management of HER2+ BC patients, such as the most adequate duration of trastuzumab therapy, the optimal chemotherapy regimen that should be combined with trastuzumab, and the addition of a second anti-HER2 agent. Growing evidences suggest that some HER2+ BC patients may not need chemotherapy. If these patients could be recognized upfront, optimal response could potentially be reached with HER2-targeted therapy alone.